Static harmonization of dynamically harmonized Fourier transform ion cyclotron resonance cell. Issue 4 (August 2017) - Zhdanova, Ekaterina; Kostyukevich, Yury; Nikolaev, Eugene
Static harmonization in the Fourier transform ion cyclotron resonance cell improves the resolving power of the cell and prevents dephasing of the ion cloud in the case of any trajectory of the charged particle, not necessarily axisymmetric cyclotron (as opposed to dynamic harmonization). We reveal that the Fourier transform ion cyclotron resonance cell with dynamic harmonization (paracell) is proved to be statically harmonized. The volume of the statically harmonized potential distribution increases with an increase in the number of trap segments.